Seizure Thresholds in Elderly Patients Treated with Electroconvulsive Therapy for Major Depressive Disorder: A Review - A. van Waarde, Jeroen; C. van der Mast, Rose (Current Psychiatry Reviews, 2010)
Objective: Electroconvulsive therapy (ECT) is effective and generally safe in depression. Its effectiveness and side effects are suggested to be related to the electrical stimulus administered relative to the seizure threshold. Since aging seems to raise the seizure threshold in ECT, we reviewed the literature for evidence correlating advanced age and seizure threshold, and for hypotheses explaining why seizure thresholds might raise with age. Methods: Pubmed, PsychINFO, three standard works on ECT, and cross-references were searched for studies investigating seizure thresholds and/or associated factors in elderly depressed patients. Results: A total of 406 possibly relevant articles were found, of which 27 studies could be included. One very recently published study was included afterwards because of its significance. Aging was moderately associated with a raised initial seizure threshold with correlation coefficients ranging from 0.30 to 0.64 (p<0.05). Also, seizure thresholds in elderly patients were more likely to raise during the ECT course. Reported hypotheses for these clinical phenomena include a decrease of neuroexcitability, changes in morphologic and functional characteristics of the brain, somatic comorbidity, and concomitant medication use. Conclusion: To optimize ECT in elderly patients, hypotheses and suggestions for further research are proposed regarding the moderate correlation between advanced age and initial seizure threshold and the rise in seizure threshold during the ECT course.
Keywords: Aging